An evaluation of the resource based view strategies adopted by furniture manufacturing SMEs in Zimbabwe - Mapetere, Denver; Manhiwa, Thelma E R (IJECM Pub UK, 2021)
The study sort to establish the resource based approaches that have been adopted by SMEs in the furniture manufacturing industry and their impact on production output. Data for the study was collected from 69 owner/managers in the furniture manufacturing cluster industry located at Mkoba 6, Mtapa and DST complex in Gweru (the third largest city in Zimbabwe). The study deployed a structured questionnaire for data collection. A 100% response rate was obtained from the study and thus allowed the study to make conclusions and generalize the study results to the furniture manufacturing sector. The study made the findings that resource based strategies adopted by SMEs in the sector are not providing desired outcomes as shown by the continuous decline in production output. Results show that SMEs in the manufacturing sector do not have the capacity to upgrade their production equipment, have limited knowledge on new production and operations management techniques as they do not attend production oriented workshops which has affected their production output volume and quality. More so, SMEs in the manufacturing sector have not been able to benefit from the use of contract labour although it is their major manpower complement. The study recommends SME owner/managers to attend training workshops to gain more knowledge on how to monitor and control production. Also, local government should assist SME in the manufacturing sector by availing industrial parks that are equipped with state of the art technologies in order to bridge the technology gaps amongst SMEs.